Hydrothermal carbonization of the wet fraction from mixed municipal solid waste: Hydrochar characteristics and energy balance. (September 2022) - Śliz, M.; Tuci, F.; Czerwińska, K.; Fabrizi, S.; Lombardi, L.; Wilk, M.
Highlights: Mixed municipal solid waste from mechanical-biological treatment plant was studied. Under sieve fraction of mixed waste was processed by hydrothermal carbonization. Various parameters temperature, reaction time and solid to water ratio were studied. Ultimate and proximate analysis proved better hydrophobic and fuel properties. Energy balance confirmed that the process may be energy self-sufficient. Abstract: Mixed municipal solid waste (MSW) may be pre-treated in a mechanical–biological treatment (MBT) plant to produce an exiting stream with improved combustible characteristics. The process also produces a second waste stream, which is generally separated on a size basis by industrial sieving equipment. It contains fractions with a high moisture content such as residual food waste, soiled paper and cardboard, and small fragments of other materials. Samples of this stream, collected at an existing plant, were characterized and processed by hydrothermal carbonization (HTC) at laboratory scale, at various temperatures (180, 200 and 220 °C), reaction times (1, 4 and 8 h) and solid to water ratios (0.15 and 0.07). The primary energy balance, on a hypothetical industrial scale, was performed. In brief, the results confirmed that the produced hydrochar was a brittle, hydrophobic, solid carbonaceous product which gave a better combustion performance as the residence time of the HTC process was increased. Moreover, the dewaterability of the carbonized waste was greatly improved when compared to raw, wet samples. The results of the primary energy balance confirmed that the energy contained in the produced hydrochar was higher than the energy consumption for the process itself, under all the HTC working conditions. The energy consumed in the process was in the range of 40–70 % of the energy content of the produced hydrochar.